G179(P) Emergency management of acute painful crisis in paediatric sickle cell patients; investigating analgesic treatment delays at a district general hospital. (25th October 2020) - Tsouana, E; Ominu-Evbota, K; Chaudhary, N; Clubb, R; Tuffin, N
Abstract : Aims: To evaluate the initial management of sickle cell (SC) patients presenting to our Paediatric Assessment Unit (PAU) with vaso-occlusive crisis (VOC), with focus on time to first dose of analgesia. Methods: Retrospective review of data extracted from electronic medical records for VOC cases presenting to our PAU between July 2016 to July 2019. Multi-linear logistic regression analysis was performed to investigate the effect of various parameters on times to analgesia. Results: A total of 95 VOC cases from 52 unique patients were analyzed. Demographics and clinical characteristics are demonstrated in table 1 . Time to analgesia was over the 30-minute standard in 63% of cases. The mean time from arrival to administration of analgesia was 54 minutes and from prescription to administration was 11 minutes. For the majority of patients (89.5%), initial analgesia included a fast-acting opiate (intranasal diamorphine or fentanyl lozenges). Receiving analgesia within 30 minutes of arrival was significantly associated with high pain score on presentation (p=0.06). There was no significant association with mode of arrival (p=0.47), time of presentation (p= 0.7) or the use of an integrated care pathway tool (p=0.13). Although age overall did not have a significant effect (p=0.36), subgroup analysis showed that the 12–16 years age group was more likely to receive analgesia late (p=0.04). Conclusions: Door-to-analgesia times were often prolonged for paediatric SC patients presenting with VOC. High pain score on arrival was linked with shorter times to analgesia, but most other parameters examined did not significantly affect times to analgesia. Targeted quality improvement projects for timely emergency pain management in paediatric SC patients are needed, with particular emphasis on the 12–16 years age group, as it appears to be particularly susceptible to analgesic treatment delays.